Global Climate Change: A Threat To Food Security And Environmental Conservation - Agbogidi, O. M. (Zenodo, 2011)
Rapid socio-economic changes in some developing countries like India, China, etc., are influencing dramatically the fuel consumption pattern world over. An increase of 880 TWh of electricity consumption in transport in 2030 compared with the Reference Scenario, of which 90% occurs in PLDVs, results in about 250 Mt of additional CO2 emissions. The rise in the amount of CO2 in the atmosphere is 1.0 – 3.50C (1PCC, 2007a). If emissions of greenhouse gases, and in particular CO2, continue unabated the enhanced greenhouse effect may alter the world’s climate system irreversibly. This review attempted to examine how climate change constitutes a threat to food security and environmental conservation. Climate change (CC) refers to changes in modern climate. It reflects abnormal variations to the expected climate within the earth’s atmosphere and subsequent effects on other parts of the earth. It is emphasized that CC poses a threat to food security as it impacts on natural systems and resources through erratic rainfall patterns, heightened temperature and susceptibility to pest and disease outbreaks hence decreasing crop yields and consequently increased hunger. CC negatively affects biodiversity conservation and management through exacerbated drought conditions, increased risk of wildfires leading to some extreme events like heat, waves, river and coastal flooding, landslides, storms, hurricanes and tornadoes which culminate in environmental degradation. For its effects to be reduced establishment of more forest plantations and maintenance of the existing natural and artificial forests should be encouraged. Saving biodiversity in the form of standing forests and interact lands can help prevent climate change and help communities and natural areas cope with a changing planet. At the same time, helping nature become more reification climate change through a combination of management restoration and protection strategies will help prepare places, plants, animals and people for climatic change successful adoption of living system can help ensure their ability to support the needs of people and better withstand future changes.
Keywords: Climate change; greenhouse gas; food security; biodiversity decimation; environmental degradation